Extrato de barbatimão e células mononucleares autólogas no tratamento de feridas excisionais de coelhos - Rodrigues, Danilo Ferreira (2015)
In Veterinary Medicine treatment of skin wounds can be costly, slow and ineffective in patients with disadvantageous factors such as the elderly, diabetics, obese, comatose, malnourished, burned, and with infection process. The search for innovative and effective techniques that favor the healing process, promotes a series of scientific studies around the world. Promising results were obtained using the phytotherapy with barbatiman (Stryphnodendron adstringens) and autologous bone marrow mononuclear cells. However, there are no reports describing the association of these therapies in wounds. The aim of this study was to determine if the treatment of excisional wounds in rabbits (Oryctolagus cuniculus) is optimized by barbatiman extract associated with autologous bone marrow mononuclear cells, and to compare these therapies used alone. Initially, the wounds were evaluated clinically by the intensity of parameters such as hyperemia, bleeding, discharge, crusting, epithelialization of the wound area and healing time, plus the histological evaluation, with observation of polymorphonuclear cells, mononuclear cells, fibroplasia and angiogenesis, in addition to quantitation of collagen fibers. Then, we evaluated whether the therapies aided in the study of cell proliferation. This study employed clinical evaluation, morphometric, histological and histochemical methods in the wounds. We observed that, in the initial phase of the healing, barbatiman stimulates the production of collagen fibers and promotes the formation of more exuberant crusts on the wounds and remodeling phase favors the orientation of collagen fibers, but when combined with autologous bone marrow mononuclear cells it does not stimulate the wound healing in rabbits.